Stone Free Rate of Lower Pole Calyceal Stone Versus Other Calyces in Retrograde Intrarenal Surgery - Shah, Rajiv; Kandel, Tika Devi; Adhikari, Deepak (Journal of College of Medical Sciences-Nepal, 2023)
Background: Miniaturization of endoscopic instruments has gained wide popularity in the treatment of renal calculi. Retrograde intra-renal surgery (RIRS) and laser in combination has already proven their superiority when compared to other modalities in the treatment of renal calculi. This study was conducted to assess the stone-free rate (SFR) of lower pole calyceal stone versus other pole calyces in RIRS. Methods: This retrospective study analyzed the stone free rate of lower pole calyx stone versus other pole calyces in retrograde intra renal surgery (RIRS) adults above 15 years of age from March 2021 to February 2022 at Chitwan Medical College and Teaching Hospital, Nepal. The stone-free rate was assessed descriptively on post operative complications, stone size, operative time, hospital stay, and need for the second procedure. Results: A total of 62 patients underwent retrograde intrarenal surgery. The mean age of the study population was 38.41 ± 10.54years in the lower caliceal group against 39.09 ±13.53 years with p value of 0.829.The mean hounsfield of lower caliceal stone was 1023.31±252.96 to that of other caliceal stones 1004.00±349.22 with p value of 0.806. The sizes of the stones were 11.07±2.10 mm in lower caliceal stones versus 10.67±2.51mm in other caliceal stones with p value of 0.507. The duration of operation time in 1st group was 63.82±23.57minutes to that of 65.93±28.96 in 2nd group with p value of 0.756. The hospital stay in lower caliceal stones were 6.13±1.43days to that of other caliceal stones 5.87±0.99 with significant p value of 0.412. There were no major complications in both arms. The stone free rate was 25 (86.2%) in lower caliceal stones as compared to 31(93.93%) in other caliceal stones with no significant p value of 0.405. Conclusions: Retrograde intrarenal surgery is a better procedure that continues to undergo significant advancements. It is a technically safe and effective procedure for the treatment option for treating the lower pole calyx calculus with optimal post-surgical morbidity and stone-free rate.